Investors Behaviour in Various Investment Avenues in India-A Review - Shekhar, Shashank (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
This study deals with the behaviour of the investor to identify the better investment avenues available in India. The investment strategy is a plan, which is created to guide an investor to choose the most appropriate investment portfolio that will help them to achieve their financial goals within a particular period of time. By increasing personal wealth, investing can contribute to higher, overall economic growth and prosperity. The process of investing helps companies where they can raise their capital through financial markets. Specific types of investments provide other benefits for the investor, corporate as well as the society. The Indian investors are very much aware about the concept of portfolio allotments and risk and return of the investment. The mantra of the investment is „‟Prevention is better than Cure” which is expected with more income but less risk. KEYWORDS:Investment Strategy, Investment Portfolio, Risk and Return, wealth management investment alternatives